Risk of postnatal depression or suicide after in vitro fertilisation treatment: a nationwide case–control study. (10th December 2015) - Vikström, J; Sydsjö, G; Hammar, M; Bladh, M; Josefsson, A
Abstract : Objective: To examine whether women who undergo in vitro fertilisation (IVF) treatment are at greater risk of postnatal suicide or postnatal depression (PND) requiring psychiatric care, compared with women who conceive spontaneously. Design: Case–control study using data from national registers. Setting: Sweden during the period 2003–2009. Population: Cases were 3532 primiparous women who had given birth following IVF treatment. An aged‐matched control group of 8553 mothers was randomly selected from the medical birth register. Methods: Logistic regression analyses were performed with PND as the outcome, and with known risk factors of PND as well as IVF/spontaneous birth as covariates. Main outcome measures: Postnatal depression (PND), defined as diagnoses F32–F39 of the tenth edition of the International Classification of Diseases (ICD–10), within 12 months of childbirth. Results: Initial analyses showed that PND was more common in the control group than in the IVF group (0.8 versus 0.4%; P = 0.04); however, these differences disappeared when confounding factors were controlled for. A history of any psychiatric illness ( P = 0.000; odds ratio, OR = 25.5; 95% confidence interval, 95% CI = 11.7–55.5), any previous affective disorder ( P = 0.000; OR = 26.0; 95% CI = 10.5–64.0), or specifically a personality disorder ( P = 0.028; OR = 3.8; 95% CI = 1.2–12.7) increased the risk of PND. No woman in either group committed suicide during the first year after childbirth. Conclusions: Whereas mothers who receive IVF treatment are not at increased risk of PND, the risk is increased among mothers with a history of mental illness. Tweetable abstract: A Swedish study on 3532 women showed that IVF treatment does not increase the risk of postnatal depression. Tweetable abstract: A Swedish study on 3532 women showed that IVF treatment does not increase the risk of postnatal depression.